2011
DOI: 10.1017/s0967199410000663
|View full text |Cite
|
Sign up to set email alerts
|

Insulin–transferrin–selenium (ITS) improves maturation of porcine oocytes in vitro

Abstract: The objective of this study was to determine if insulin-transferrin-selenium (ITS) promoted a nuclear and cytoplasmic maturation of porcine oocytes that better supports subsequent embryonic development. The rate of oocyte in vitro maturation (IVM) in an experimental group treated with hormones for 42 h was significantly increased compared with that in a control group without hormone treatment (47.8% vs. 11.7%, respectively, p < 0.05). Following reduction of the hormone treatment period from 42 h to 21 h, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…This supported the paradigm that insulin facilitates cellular glucose uptake, which may stimulate proliferation. Taken together with data demonstrating that insulin increases in vitro maturation of porcine oocytes and formation of blastocysts (31,32), our evidence strengthens the claim that insulin is a vital growth stimulus and is important in normal embryo development.…”
Section: Discussionsupporting
confidence: 86%
“…This supported the paradigm that insulin facilitates cellular glucose uptake, which may stimulate proliferation. Taken together with data demonstrating that insulin increases in vitro maturation of porcine oocytes and formation of blastocysts (31,32), our evidence strengthens the claim that insulin is a vital growth stimulus and is important in normal embryo development.…”
Section: Discussionsupporting
confidence: 86%
“…Hochedlinger et al reported that the development of reconstructed oocytes into blastocysts was particularly sensitive to the cell-cycle stage and physical condition of the transferred nuclei [41]. In previous studies, we also found that oocyte nuclear modifications and cytoplasmic maturation underwent dramatic alterations during in vitro maturation (around 42 h) that affected subsequent embryo development [42]. The studies of the cell cycle profile of mouse iPS cells cultured with LIF showed that LIF-induced DNA synthesis caused the high percentage of iPS cells in S and G2 phases [43].…”
Section: Discussionsupporting
confidence: 58%
“…After culturing COCs in maturation media supplemented with 7,8-DHF, although there were no significant differences in PB extrusion, the cytoplasmic maturation was increased in 1 μM-treated group compared with the other groups. Nuclear and cytoplasmic maturation are normally coordinated, but some processes of cytoplasmic maturation related to successful preimplantation development probably occur without coordination with nuclear maturation [41], and cytoplasmic quality in IVM oocytes plays a major role in the reconstruction of embryonic development [42]. Moreover, the level of GSH was significantly increased and that of ROS was decreased in the group treated with 1 μM 7,8-DHF, and it is supposed that intracellular redox metabolism [43] was effectively regulated in that group.…”
Section: Discussionmentioning
confidence: 99%